Integration of full-length transcriptomics and targeted metabolomics to identify benzylisoquinoline alkaloid biosynthetic genes in Corydalis yanhusuo. (10th January 2021) - Xu, Dingqiao; Lin, Hanfeng; Tang, Yuping; Huang, Lu; Xu, Jian; Nian, Sihui; Zhao, Yucheng
Abstract: Corydalis yanhusuo W.T. Wang is a classic herb that is frequently used in traditional Chinese medicine and is efficacious in promoting blood circulation, enhancing energy, and relieving pain. Benzylisoquinoline alkaloids (BIAs) are the main bioactive ingredients in Corydalis yanhusuo . However, few studies have investigated the BIA biosynthetic pathway in C. yanhusuo, and the biosynthetic pathway of species-specific chemicals such as tetrahydropalmatine remains unclear. We performed full-length transcriptomic and metabolomic analyses to identify candidate genes that might be involved in BIA biosynthesis and identified a total of 101 full-length transcripts and 19 metabolites involved in the BIA biosynthetic pathway. Moreover, the contents of 19 representative BIAs in C. yanhusuo were quantified by classical targeted metabolomic approaches. Their accumulation in the tuber was consistent with the expression patterns of identified BIA biosynthetic genes in tubers and leaves, which reinforces the validity and reliability of the analyses. Full-length genes with similar expression or enrichment patterns were identified, and a complete BIA biosynthesis pathway in C. yanhusuo was constructed according to these findings. Phylogenetic analysis revealed a total of ten enzymes that may possess columbamine-O-methyltransferase activity, which is the final step for tetrahydropalmatine synthesis. Our results span the whole BIA biosynthetic pathway in C. yanhusuo . Our full-length transcriptomic data will enable further molecular cloning of enzymes and activity validation studies.